A Prospective Study on the Relationship Between Driving and Non-occupational Computer Use With Risk of Dementia - Takeuchi, Hikaru; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2022)
Sedentary behaviors have been associated with the risk of dementia in older adults. Whether driving and computer use are associated with the risk of dementia in older adults is an important research question. Participants of a longitudinal cohort study that included European middle- and old-aged adults at baseline (2006–2010) who had not been diagnosed with dementia before five years after baseline and had not died within five years after baseline were followed up (until 2018) and analyzed.　Associations between driving and nonoccupational computer use time measured by the questionnaire at baseline and incident dementia five years after baseline were analyzed after correcting for confounding variables. Each analysis included approximately 370,000 participants and 1000 cases. According to Cox proportional hazard models that divide subjects into four groups of habit duration levels (a, 0 h; b, less than an hour, 1 h; c, 2 h, 3 h; d, 4 h or more, per/day), the group with 0 h < driving time ≦ 1 h at baseline exhibited a significantly lower risk of incident dementia than the other groups. In addition, in the analysis of nonoccupational computer use duration, the 0 h group exhibited a significantly higher risk than the other groups. Our results indicate that different sedentary behaviors have different associations with dementia risk over time and have no simple dose–response relationship with dementia risk. Sedentary behavior risk assessments must consider these factors.